Studi Deskriptif Tentang Praktik Bagi Hasil Mukhabarah Dan Relevansinya Dengan Konsep Akuntansi Syariah: Studi Pada Petani Di Desa Maduri - Wiwi Astiawati; Muhammad Fakhri Amir; Masyhuri Masyhuri (ISAS, 2026)
This research aims to describe the profit-sharing practice of the mukhabarah contract and analyze its relevance to the concept of sharia accounting among farmers in Maduri Village. The selection of the sharia accounting concept is based on the characteristics of the mukhabarah contract as a profit-sharing cooperation that emphasizes the values of justice, honesty, transparency, and accountability. This research employs a qualitative approach and field research methods, using data collection techniques such as interviews, observations, and documentation. The research results show that the practice of mukhabarah profit-sharing is carried out through verbal agreements based on trust and community customs, in which the landowner provides only the land, while the farmers bear all costs and labor. The division of the harvest uses 2:1 or 60:40 ratio, with a larger share for the farmers, without written records. Based on the values and principles of Sharia accounting, this practice is relevant to it reflects the principles of justice, honesty, transparency, and trustworthiness. However, it is not yet fully optimal in terms of accountability due to the lack of a clear recording system. This research recommends that the profit-sharing practice of mukhabarah be conducted with clear agreements and accountability in accordance with the principles of Sharia accounting. Keywords: Mukhabarah, Profit Sharing, Sharia Accounting, Relevance